DC's legends of tomorrow. The complete second season [videorecording (DVD)] - Berlanti, Greg; Guggenheim, Marc; Kreisberg, Andrew, 1971-; Klemmer, Phil (DC's Legends of tomorrow, 2017)
After saving the world from Vandal Savage, the Legends of Tomorrow are now charged with protecting time, past, present, and future, taking them across history and up against a threat unlike any humanity has ever known.